Perceptions of selected Master of Library and Information Science graduates on the possible implementation of the Library and Information Science Ph. D. course in Ateneo de Manila University - Lumbre, Nathaniel B.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
The study focused on the market feasibility of the LIS Ph.D. course of the Ateneo de Manila University. The study intended to determine and analyze the perceptions of Master of Library and Information Science graduates on the possible Implementation of LIS doctorate course in AdMU. A total of 17 respondents, who are all MLIS degree holders from the University of the Philippines School of Library and Information Studies, answered the online survey questionnaire administered by the researcher.
The data gathered revealed that the LIS course in Ph.D. is a personal need and is not a requirement in their current affiliated institutions. Also, most of the respondents agreed that the LIS in Ph.D. should be offered in the Philippines. "Career development" and "location and accessibility" were the two greatest factor considered by the MLIS graduates upon enrolling in the Ph.D. in LIS that AdMU will offer. Most of the respondents are neutral when it comes to improving the status of the LIS profession in the country by AdMU spearheading the implementation of the LIS Ph.D. course. On the other hand, there are no strong responses as to whether the offering of Ph.D. in LIS is a solution to going overseas for doctorate courses. The researcher also concluded that the implementation of the Ph.D, in LIS at the AdMU may help generate positive perceptions on the LIS profession in the country but will not solve the problems of MLIS graduates going out of the country for post-graduate LIS degrees.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Library education (Continuing education) -- Philippines -- Quezon City; Degrees, Academic; Library science